Stable SiO2–TiO2 composite-based nanofluid of improved rheological behaviour for high-temperature oilfield applications. Issue 1 (2nd January 2020) - Kumar, Ravi Shankar; Sharma, Tushar
ABSTRACT: Nanofluid synthesis in pure water is associated with premature settlement resulting in least dispersion stability. Therefore, in this study, polyacrylamide (PAM) is used as viscosity enhancer to improve dispersion stability of nanofluid stabilized by composites of silica and titania. Different techniques such as dynamic light scattering measurements, electrical conductivity, scanning electron microscopy, and rheological studies are used to support the analysis. The use of silica and titania nanoparticles together with PAM has additional advantage over particle agglomeration, and thus, the dispersion stability improved. Further, nanofluid stabilized by composites of silica and titania was tested for rheological measurements at 90°C to find nanotechnology applicability in high-temperature applications. The shear-thinning behaviour of nanofluids at high temperature (90°C) was least affected by shear deformation and reduced to 0.48 mPa.s at higher shear rate (4200 s −1 ), while shear thinning of PAM solution seriously varied with increasing shear deformation and takes the edge of 0.0005 mPa.s at higher shear rate (4200 s −1 ). In addition, the thermal stability of nanofluids was better due to slight decrease in viscosity with increasing temperature, which makes them suitable to be utilized at high-temperature applications in widespread industrial areas including oilfield where the temperature becomes a major factor.